The Book of the Lover and the Beloved : lo libre de amich e amat librum amici et amati - Llull, Ramon, 1232?-1316 (Hispanic classics. Catalan literature., 1996)
Ramon LLull (1232-1316) was born the son of a prosperous Catalan merchant and spent his youth pursuing worldly pursuits, until a series of powerful visions of Christ moved him to devote his life entirely to serving God. One of his lifelong ambitions was to write a book to counter the "errors of the infidels", to which end he studied Arabic and immersed himself in whatever arabic texts he could obtain. The Book of the Lover is one of the most celebrated works of medieval mystical literature offering a uniquely expressed and moving testimony to the soul's quest for union with God. The 365 paragraphs of "moral metaphors" intended for daily meditation, are written in the style of the Muslim sufis who offer words of love and brief exampla that inspire great devotion. Professor Johnston concisely explains the peculiarities of Llull's idiosyncratic theological and philosophical system and offers the most comprehensive assessment to date of his debt to the Islamic tradition of devotional discourse. In addition, brief notes help to guide the reader's appreciation of the spiritual insight that Llull sought to stimulate with his text. Contains original Latin and Catalan text, translation and commentary.